MOOD SYSTEM IN THE LITTLE PRINCE: A SYSTEMIC FUNCTIONAL LINGUISTICS APPROACH - Chesya Purba; Grace Chelvia Ginting; Stephani Anastasia; Giovanni Goh; Nurlela Majrul (ELITERATE : Journal of English Linguistics and Literature Studies, 2026)
This study examines the interpersonal meaning realized through the mood system in The Little Prince by Antoine de Saint-Exupéry using the framework of Systemic Functional Linguistics (SFL). Drawing on the theories proposed by M.A.K. Halliday and further elaborated by Suzanne Eggins as well as Linda Gerot and Peter Wignell, this research focuses on how mood choices declarative, interrogative, and imperative are used by the main characters, namely the Prince and the Pilot, to construct interpersonal relationships.The data were taken from selected dialogues in the novel, particularly those that highlight interactions between the two main characters. The analysis applies the concept of the clause as exchange, identifying the Mood element (Subject and Finite) and Residue to determine the type and function of each clause. The findings reveal that declarative clauses are predominantly used to convey information and express philosophical reflections, while interrogative clauses indicate curiosity and exploration, especially from the Prince. Imperative clauses appear less frequently but reflect moments of request or subtle authority.Overall, the study shows that mood choices play a significant role in shaping the interpersonal dynamics between characters. The Prince tends to use more interrogatives, reflecting innocence and curiosity, whereas the Pilot relies more on declaratives, indicating experience and narrative control. This study contributes to SFL-based literary analysis by highlighting how grammatical choices can reveal deeper meanings and character relationships within a narrative text.